Reasonable adjustments to provide equitable and inclusive assessment, screening and treatment of osteoporosis for adults with intellectual disabilities: A feasibility study. Issue 2 (2nd September 2018) - Finlayson, Janet; De Amicis, Leyla; Gallacher, Stephen; Munro, Robin; Crockett, Jennifer; Godwin, Jon; Feeney, Wendy; Skelton, Dawn A.
Abstract: Background: People with intellectual disabilities are a high risk population for developing osteoporosis and fragility fractures, yet they experience barriers to accessing dual‐energy x‐ray absorptiometry (DXA) bone mineral density (BMD) screening and fracture assessment. Reasonable adjustments are a statutory requirement in the UK, but there is a paucity of evidence‐based examples to assist their identification, implementation and evaluation. Method: Thirty adults with intellectual disabilities underwent DXA BMD screening and fracture risk assessment. Reasonable adjustments were identified and implemented. Results: The presence of osteopenia or osteoporosis was detected in 23 out of 29 (79%) participants. Osteoporosis professionals report that 17 of 18 reasonable adjustments identified and implemented are both important and easy to implement. Conclusion: Adults across all levels of intellectual disabilities can complete DXA BMD screening with reasonable adjustments. Widely implementing these reasonable adjustments would contribute to reducing inequalities in health care for adults with intellectual disabilities.